2021
DOI: 10.31703/gssr.2021(vi-i).16
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Agricultural Performance of Districts of Punjab Based On Composite Agricultural Indicators Using Grey Relational Analysis

Abstract: The province of Punjab is considered the breadbasket of Pakistan. This study is aimed to evaluate and hierarchicalize the districts of Punjab based on agricultural indicators. It follows a ranking approach that uses secondary cross-sectional data obtained from Punjab Development Statistics 2016. This study has employed Grey System Theory and used GRA. It is a seminal study that uses a unique methodology that has integrated thirteen different indicators of agricultural development in one mathematical model and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Ertuğrul et al (2016) focused on ranking of Turkish universities, and compared them on the basis of five different indicators using the secondary data sets and rationalized the ranking of universities. Qazi et al (2021a) evaluated the immediate response of the countries to the COVID-19 pandemic, and then ranked and classified them on the basis of grey relational grades taking real-time data from "Worldometer." Giannakitsidou et al (2020) focused on the environmental and circular economic performance of European countries using data envelopment analysis, and concluded that Belgium is one of the best performers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ertuğrul et al (2016) focused on ranking of Turkish universities, and compared them on the basis of five different indicators using the secondary data sets and rationalized the ranking of universities. Qazi et al (2021a) evaluated the immediate response of the countries to the COVID-19 pandemic, and then ranked and classified them on the basis of grey relational grades taking real-time data from "Worldometer." Giannakitsidou et al (2020) focused on the environmental and circular economic performance of European countries using data envelopment analysis, and concluded that Belgium is one of the best performers.…”
Section: Discussionmentioning
confidence: 99%
“…The abridged procedure of GRA includes 1) extraction of data, 2) normalization of data, 3) generation of reference series, 4) calculation of deviation sequence, 5) calculation of grey relational coefficients, 6) calculation of grey relational grades, and 7) generation of ranking list. As an augmentation of GRA, a classification based on grey relational grades is also introduced (Qazi et al, 2021a). Although we have adopted algorithm of GRA from Ertuğrul et al (2016), it is still found to be beneficial to reiterate the algorithm (Annex 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Step 4: Produce the grey relational grade The grey relational grade (GRG) reflects the closeness of the tested materials to the ideal species, which is calculated by Eq. ( 17) (Qazi et al 2021):…”
Section: Grey Relational Analysismentioning
confidence: 99%